2021
DOI: 10.1021/acssuschemeng.1c06659
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Dehydration with Ionic Liquids from Molecular Insights to Process Intensification

Abstract: The ethanol (EtOH) dehydration process using ionic liquids (ILs) as entrainers by extractive distillation integrated with a heat pump was systematically investigated from the molecular level to the process scale. [BMIM][Cl] was selected as the appropriate entrainer from a variety of [Cl] − -based ILs by achieving vapor−liquid equilibrium (VLE) experiments for binary systems of EtOH−IL and water (H 2 O)−IL. The VLE behavior of a ternary EtOH−H 2 O−IL system demonstrates that the azeotropic phenomenon of the bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The intermolecular interaction and microstructure are analyzed by density functional theory (DFT) method using the Gaussian 09 (version E.01) 49,50 . The geometry of each compound is optimized at the B3LYP/6‐31 + G (d, p) theoretical level, 51 along with DFT‐D3(BJ) dispersion corrections 52 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intermolecular interaction and microstructure are analyzed by density functional theory (DFT) method using the Gaussian 09 (version E.01) 49,50 . The geometry of each compound is optimized at the B3LYP/6‐31 + G (d, p) theoretical level, 51 along with DFT‐D3(BJ) dispersion corrections 52 .…”
Section: Methodsmentioning
confidence: 99%
“…The intermolecular interaction and microstructure are analyzed by density functional theory (DFT) method using the Gaussian 09 (version E.01). 49,50 The geometry of each compound is optimized at the B3LYP/6-31 + G (d, p) theoretical level, 51 along with DFT-D3 (BJ) dispersion corrections. 52 As the calculation of {DSIL + o-xylene/ n-octane} interaction energies at different molar ratios of parent ILs is difficult, geometric structures between each parent IL and o-xylene/ n-octane are optimized, followed by the interaction energy calculation as a reference for the DSILs-involved systems.…”
Section: Quantum Chemistry Calculationmentioning
confidence: 99%
“…At the molecular level, molecular dynamics simulations such as density functional theory (DFT) aim to reveal the IL–azeotrope separation mechanism and guides for screening and designing of excellent ILs. The phase equilibrium level consists of three aspects. One is measurement and correlation of isobaric/isothermal VLE of IL–azeotrope systems.…”
Section: Introductionmentioning
confidence: 99%
“…Process simulation technology can provide guidance for designing practical industrial scale separation processes. , It can also determine the industrial application value of solvents through economic consumption and environmental performance . For instance, Han et al proposed modified extractive distillation (ED) processes with heat pumps using [C 4 mim]­[Cl] as an entrainer for separating ethanol and H 2 O. Zhao et al optimized ED process to reduce the total annual cost (TAC) and gas emissions of separating ternary azeotropes. Zhang et al reported that using [C 4 mim]­[NO 3 ] to separate methyl tert -butyl ether and ethanol presented a gentler separation process and lower TAC compared to dimethyl sulfoxide.…”
Section: Introductionmentioning
confidence: 99%